AI ACCEPTANCE AND USE IN MATHEMATICS PRE-SERVICE TEACHERS: A THEORY OF PLANNED BEHAVIOUR APPROACH - Hilman Qudratuddarsi; Jumriani; Eli Meivawati; Saraswathy a/p Ramasundrum (Mathematics Education and Application Journal (META), 2025)
Artificial Intelligence (AI) is increasingly integrated into education, including mathematics learning, yet its successful implementation largely depends on teachers’ acceptance and readiness. This study aims to examine the determinants of AI acceptance and use among pre-service mathematics teachers by employing the Theory of Planned Behaviour (TPB), which comprises Attitude (AT), Social Norms (SN), Perceived Behavioral Control (PBC), Behavioral Intention (BI), and AI Use (AIU). A quantitative, cross-sectional survey design was used. Data were collected from 427 Generation Z pre-service mathematics teachers enrolled in three Indonesian universities using an online questionnaire. The instrument was adapted from a previously validated TPB-based scale, and data were analyzed using PLS-SEM with SmartPLS. The measurement model demonstrated excellent reliability and validity, and the structural model indicated very good fit (SRMR = 0.044). All hypothesized relationships were supported (p < 0.001). SN emerged as the strongest predictor of BI, followed by AT and PBC, while BI was the most powerful determinant of AIU (β = 0.849). These findings highlight the central role of social influence, positive attitudes, and technological efficacy in shaping pre-service teachers’ intentions and actual use of AI. The study implies that teacher education programs should design courses and practicum experiences that foster positive beliefs about AI, enhance digital competence, and leverage supportive social environments to promote meaningful AI integration in mathematics classrooms.   Keywords: Artificial Intelligence Acceptance, Artificial Intelligence Use, Educational technology, Mathematics Pre-service Teacher, Theory of Planned Behaviour,   Artificial Intelligence (AI) semakin banyak dimanfaatkan dalam pendidikan, termasuk pada pembelajaran matematika, namun keberhasilan integrasinya sangat bergantung pada penerimaan dan kesiapan calon guru. Penelitian ini bertujuan menganalisis faktor-faktor yang memengaruhi penerimaan dan penggunaan AI pada calon guru matematika menggunakan kerangka Theory of Planned Behaviour (TPB), yang mencakup Attitude (AT), Social Norms (SN), Perceived Behavioral Control (PBC), Behavioral Intention (BI) dan AI Use (AIU). Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross-sectional. Sebanyak 427 calon guru matematika generasi Z dari tiga universitas di Indonesia berpartisipasi melalui pengisian kuesioner daring. Instrumen diadaptasi dari penelitian terdahulu berbasis TPB dan dianalisis menggunakan PLS-SEM melalui SmartPLS. Hasil menunjukkan bahwa model pengukuran memiliki reliabilitas dan validitas yang sangat baik, serta model struktural menunjukkan kelayakan yang tinggi (SRMR = 0,044). Semua hipotesis didukung secara signifikan (p < 0,001). SN muncul sebagai prediktor terkuat BI, diikuti AT dan PBC, sedangkan BI menjadi penentu utama AIU (β = 0,849). Temuan ini menegaskan pentingnya dukungan sosial, sikap positif, dan efikasi teknologi dalam mendorong niat dan perilaku penggunaan AI. Implikasinya, program pendidikan guru perlu merancang pelatihan dan pengalaman praktik yang menumbuhkan sikap positif, meningkatkan kompetensi digital, dan memanfaatkan pengaruh sosial yang konstruktif terhadap penggunaan AI dalam pembelajaran matematika.   Kata Kunci: Artificial Intelligence Acceptance, Artificial Intelligence Use, Educational technology, Mathematics Pre-service Teacher, Theory of Planned Behaviour.